2011
DOI: 10.1152/jn.00580.2010
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdala responds robustly to social calls: spiking characteristics of single unit activity

Abstract: Vocalizations emitted within a social context can trigger call-specific changes in the emotional and physiological/autonomic state of the receiver. The amygdala is implicated in mediating these changes, but its role in call perception remains relatively unexplored. We examined call and pitch selectivity of single neurons within the basolateral amygdala (BLA) by recording spiking activity in response to 5 pitch variants of each of 14 species-specific calls presented to awake, head-restrained mustached bats, Pte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 108 publications
1
22
1
Order By: Relevance
“…The ratio of stimulus-selective cells to all recorded cells was larger in the surrounding arcopallium (34.1%) than in the TnA (20.3%), suggesting that neurons in this area can represent behavioral relevance of stimuli and be involved in recognizing vocalizations and controlling successive behaviors. Recently, neural activity in the amygdala, especially in the lateral or basolateral subdivision, has been investigated in rodents and bats [Naumann and Kanwal, 2011;Gadziola et al, 2012Gadziola et al, , 2016Parsana et al, 2012;Peterson and Wenstrup, 2012;Grimsley et al, 2013]. In the rat lateral amygdala, it has been known that neurons respond to the cue tones in the fear conditioning [LeDoux et al, 1990].…”
Section: Evolutional Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of stimulus-selective cells to all recorded cells was larger in the surrounding arcopallium (34.1%) than in the TnA (20.3%), suggesting that neurons in this area can represent behavioral relevance of stimuli and be involved in recognizing vocalizations and controlling successive behaviors. Recently, neural activity in the amygdala, especially in the lateral or basolateral subdivision, has been investigated in rodents and bats [Naumann and Kanwal, 2011;Gadziola et al, 2012Gadziola et al, , 2016Parsana et al, 2012;Peterson and Wenstrup, 2012;Grimsley et al, 2013]. In the rat lateral amygdala, it has been known that neurons respond to the cue tones in the fear conditioning [LeDoux et al, 1990].…”
Section: Evolutional Perspectivementioning
confidence: 99%
“…Grimsley et al [2013] demonstrated that neurons in the mouse basolateral amygdala are activated when listening to behaviorally aversive vocalizations and that the activity is modulated by visual cues associated with predation. In bats, the neurons in the lateral [Gadziola et al, 2012] or basolateral amygdala [Naumann and Kanwal, 2011;Peterson and Wenstrup, 2012;Gadziola et al, 2016] respond selectively to specific social calls. Subdivision structures and corresponding function in the avian amygdala may not necessarily have evolved the same way as those of mammals.…”
Section: Evolutional Perspectivementioning
confidence: 99%
“…The present study assessed response duration using two different measures. The first measure used a sliding 20-ms average of the PSTH to analyze response duration across a block of trials, a method commonly used for assessing response duration (Bendor and Wang 2008;Naumann and Kanwal 2011). Although derived, this type of measure uses confidence intervals to take into account the trial-by-trial variance, and it provides a more faithful representation of the original raster data.…”
Section: Response Durationmentioning
confidence: 99%
“…In studies of basolateral amygdalar responses, persistent firing is observed in auditory and other sensory stimuli (Bordi and LeDoux 1992;Bordi et al 1993;Maeda et al 1992;Naumann and Kanwal 2011) but is generally not characterized. Our results show that persistent firing in the lateral amygdala has the potential to carry discriminatory information for coding social vocalizations at the single-neuron level and that duration of persistent firing carried more information for discriminating among social vocalizations than firing rate.…”
Section: Persistent Firingmentioning
confidence: 99%
See 1 more Smart Citation